Breckinridge : Statesman, Soldier, Symbol - Davis, William C., 1946- (Book collections on Project MUSE., 2015)
John C. Breckinridge rose to prominence during one of the most turbulent times in our nation's history. Widely respected, even by his enemies, for his dedication to moderate liberalism, Breckinridge's charisma and integrity led to his election as Vice President at age 35, the youngest ever in America's history. After a decade of being out-of-print, Breckinridge: Statesman, Soldier, Symbol returns as the quintessential biography of one of Kentucky's great moderates. Historian William C. Davis sheds light on Breckinridge's life throughout three key periods, spanning his career as a celebrated s.